Conceptualizing Policy on Underwater Cultural Heritage: Towards Legal Protection and Ecotourism Promotion in Karimun Jawa, Indonesia - Puspitawati, Dhiana; Fadli, Moh.; Lutfi, Mustafa; Anggoro, Syahriza Alkhoir; Rusli, Mohd Hazmi Mohd (Universitas Negeri Semarang, 2023)
Karimun Jawa Island is a promising maritime asset, enriched by abundant water resources in Central Java. However, the allure of this location poses a potential threat to the sustainable ecosystems of marine biota unless prompt government action is taken to safeguard its underwater cultural heritage. This research proposes a comprehensive policy design for legal protection and ecotourism development in Karimun Jawa, balancing economic considerations and environmental preservation. Employing a socio-legal methodology encompassing interviews, observation, and focus group discussions, the study identifies substantial challenges in managing underwater cultural heritage in Karimun Jawa. These challenges encompass over-exploitation, shipwreck theft, damage from trawlers, natural disasters, and plastic pollution. The research underscores the imperative for the government to formulate measures ensuring legal protection on international, national, and regional fronts. At the global level, immediate ratification of the Convention on the Protection of Underwater Cultural Heritage 2001 is recommended. Moreover, effective collaboration among stakeholders—central and regional governments, local communities, and maritime enterprises—is deemed crucial for sustainable, culturally informed policy formulation fostering responsible management, utilization, and protection of this unique marine heritage.